Pengaruh Penerapan Model Pembelajaran Snowball Throwing Terhadap Pembelajaran Nahwu di Madrasah Diniyah Darut Taqwa Sengonagung Purwosari Pasuruan - Masruroh (Impressive: Journal of Education, 2023)
At Madrasah Diniyah Darut Taqwa, the learning of nahwu uses the lecture method, which is considered ineffective. From here the researcher tried to experiment the effect of the snowball throwing model on nahwu learning at Madrasah Diniyah Darut Taqwa. the approach used is a quantitative approach. This type of research is the experimental pre-post-test on one sample. The research instruments used were observation, interviews, tests, and documentation, and the tools for analyzing data were using SPSS. From the results of the final calculation of the T-test research, the effect of the snowball throwing learning model on nahwu learning at Madrasah Diniyah Darut Taqwa with SPSS statistical calculations, shows the probability value sig. (2 tailed) is less than 0.05, which is 0,000, meaning that H0 is not accepted, it means that the average pretest and posttest scores are different or the learning relationship between students of Madrasah Diniyah Darut Taqwa between before and after using the snowball throwing learning model looks very far.